2015
DOI: 10.2139/ssrn.2670448
|View full text |Cite
|
Sign up to set email alerts
|

Gradual Retirement, Financial Incentives, and Labour Supply of Older Workers: Evidence from a Stated Preference Analysis

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(10 reference statements)
1
2
0
1
Order By: Relevance
“…Note that both S4 and S5 have partial retirement for either the respondent (S4) or the spouse (S5). A preference for S4 or S5 therefore also implies a preference for partial retirement, in line with what Van Soest and Vonkova (2014) and Elsayed et al (2018) found using Dutch SP data and analyzing individual preferences. For example, Van Soest and Vonkova (2014) analyzed four types of hypothetical retirement scenarios -standard retirement, late retirement, early retirement and partial retirement and found that if more exibility is added in the form of gradual retirement with an actuarially fair partial pension, almost two thirds would opt for gradual retirement.…”
Section: Figuresupporting
confidence: 85%
See 1 more Smart Citation
“…Note that both S4 and S5 have partial retirement for either the respondent (S4) or the spouse (S5). A preference for S4 or S5 therefore also implies a preference for partial retirement, in line with what Van Soest and Vonkova (2014) and Elsayed et al (2018) found using Dutch SP data and analyzing individual preferences. For example, Van Soest and Vonkova (2014) analyzed four types of hypothetical retirement scenarios -standard retirement, late retirement, early retirement and partial retirement and found that if more exibility is added in the form of gradual retirement with an actuarially fair partial pension, almost two thirds would opt for gradual retirement.…”
Section: Figuresupporting
confidence: 85%
“…The method of Stated Preferences has been commonly used in marketing and transportation sciences for many years (see, e.g., Louviere et al (2000)), and is gaining ground in economics since Barsky et al (1997) and Revelt and Train (1998). Elsayed et al (2018) and Van Soest and Vonkova (2014) apply stated preferences to labor supply and retirement decisions of individuals. The latter motivate the use of SP data from the fact that they want to analyze preferences for plans that do not yet exist (e.g., retirement after the mandatory retirement age).…”
Section: Introductionmentioning
confidence: 99%
“…Im Vereinigten Königreich befürworten 55% der Befragten ein System mit Teilfrührente und im Gegenzug eine geringere Rente zum Zeitpunkt des vollständigen Renteneintritts (Berry, 2011). In den Niederlanden hingegen zieht die Mehrzahl der Befragten weiterhin den vollständigen Übergang in den Ruhestand zum Regelrentenalter einem gleitenden Übergang vor (Van Soest et al, 2006;Elsayed et al, 2015). Der schrittweise Renteneintritt steht aber an Platz zwei der am häufigsten genannten Präferenzen, vor dem aufgeschobenen oder vorgezogenen vollständigen Übergang in den Ruhestand.…”
Section: Erhebungen Zeigen Dass Der Flexible Renteneintritt In Vieleunclassified
“…In the United Kingdom, 55% of survey respondents in the would support a system of partial early pensions in return for a lower pension when they retire in full (Berry, 2011). However, in the Netherlands, the majority of respondents still prefers full retirement at the retirement age over gradual retirement (Van Soest et al, 2006;Elsayed et al, 2015). But phased retirement is the second most frequently preferred option before late or early full retirement.…”
Section: Surveys Show That Flexible Retirement Is Popular In Many Countriesmentioning
confidence: 99%